DRIED FISH BUSINESS DEVELOPMENT STRATEGY IN BENGKULU PROVINCE - Pingki, Anadiya; Sukiyono, Ketut; Romdhon, M.Mustopa (Journal of Agri Socio Economics and Business, 2024)
Indonesia is one of the largest archipelagic countries in the world which has a wealth of territorial waters, namely fish producers. The fish is processed into dried fish by drying and salting. For the sustainability of the dried fish business in Bengkulu Province, it is necessary to carry out a business development strategy for dried fish MSMEs. The aim of the study was to examine the internal and external factors of the dried fish business and determine the priority strategy for the development of the dried fish business in Bengkulu Province. This research was conducted in Bengkulu Province in Sumber Jaya Village (Bengkulu City) and Koto Jaya Village (Mukomuko)by survaiyingand interviewing 13 dried fish producers ang 9 key informen. Data are analysed bu applyingSWOT and QSPM matrix. Utilizing maximum raw materials to meet customer demand and Utilizing technological developments are two grand srategies to develop dried fish industrieis in Bengkulu Province.